Implementasi Pembelajaran Al-Qur’an Hadis Dengan Pendekatan Holistik Integratif di MTs Ma’arif NU 02 Karangklesem - Qori Nurfadlilah, Lidya; Hermawan, M. A. (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
The holistic-integrative approach emerges as a solution to address the dichotomy between religious education and other scientific disciplines. The failure in teaching Qur'an and Hadith often stems from an educational approach that emphasizes the cognitive aspect while neglecting the affective and psychomotor domains, as well as the lack of emphasis on understanding the meaning of the material in everyday life. This highlights a gap between students’ theoretical understanding and their practical application. The aim of this study is to analyze the implementation of Qur'an and Hadith learning using a holistic-integrative approach in the eighth-grade class at MTs Ma’arif NU 02 Karangklesem. This research employs a qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation. The study findings indicate that Al-Qur’an Hadith teachers have implemented a holistic integrative approach. The holistic approach primarily focuses on cognitive and affective aspects while the psychomotor aspect still requires further development. The integrative approach is applied by teachers through lectures that incorporate Al-Qur’an Hadits content with subjects such as science, social studies, Islamic history, technology, and students personal experiences. This approach encourages students to become the center of the learning process through an active learning model.